Deceptive Debauchery: Secret Marriage and the Challenge of Legalism in Muslim-Minority Communities - Mariam Sheibani (Religions, 2023)
“Secret Marriage” is a category accommodating a range of arrangements that seek to conceal a marital union, typically from an existing spouse, the family of the bride or groom, a segment of the community, or the state. These contentious unions have seen an upsurge in recent times in Muslim-majority countries, and, more recently, in minority-Muslim communities in the West. This essay examines the phenomenon in minority communities using three interrelated lenses of analysis: the legal, the moral, and the socio-institutional. Taking this multi-faceted approach, in this essay, I first examine the legal doctrines of the four Sunni schools of law on the requirement of publicity and witness testimony in marriage before situating that legal discussion about contractual validity within a comprehensive analysis of the broader moral and religious legitimacy of entering into a secret union. I argue that while jurists stipulate disparate minimums for contractual validity, nearly all secret marriage arrangements are nonetheless considered invalid (fāsid), meaning they are incorrectly conducted by failing to meet the required conditions for the contract to produce its legal effects (ṣiḥḥa) and are also prohibited (ḥarām) in themselves or for their entailments, meaning contracting such a marriage is sinful and entails punishment. As I show, even as some jurists may make arguments that may seem to imply that some versions of secret marriage meet the basic conditions to make them technically valid, these same jurists nonetheless argue that such marriages are immoral, religiously deficient, unbecoming of a Muslim, and little more than a pretext for illicit sex. Apart from the theoretical question of whether a secret marriage meets the conditions of contractual validity, parties to a secret marriage in Muslim communities today further engage in a number of sins and transgressions and cause harms to spouses, children, parents, extended family, and the community that must also be reckoned with. The essay concludes with recommendations for how religious authorities can take steps towards regulating marriage in minority-Muslim communities, highlighting the need for public education on Muslim marriage practices that is embedded in a deeper religious morality centering the Sunna to counteract the dominant legalism in the Muslim community that underlies numerous contemporary dilemmas.